FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN MASKER SEBAGAI UPAYA PENCEGAHAN COVID-19 PADA ANAK-ANAK PANTI ASUHAN AL-AKBAR KOTA PEKANBARU - Alhidayati Alhidayati; Zulmeliza Rayid; Riri Maharani; Syukaisih Syukaisih (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
The use of masks during the Covid-19 pandemic is very important to protect yourself and others from the risk of transmitting this virus. As it is known that most of the transmission of Covid-19 is through droplets, it is felt necessary to protect yourself by using a mask. Considering that there are still many children at the Al-Akbar orphanage who do not use masks when they are in the orphanage or when they are outside the orphanage. This study aims to obtain factors related to the use of masks as an effort to prevent covid-19 in Al-Akbar orphanage children in Pekanbaru city. This research was conducted using a quantitative research type with a cross-sectional design. With the technique of sampling with Total Sampling. The population in this study were all 78 children of the Al-Akbar orphanage with a total sample of 78 respondents. Data analysis used univariate and bivariate, and the sampling technique used total sampling technique. The results showed that the proportion of respondents who used masks was 42 (53.8%). There is a relationship between knowledge variable (P-value = 0.0001) with POR 7.333 (2.997-23.175), attitude (P-value = 0.001) with POR 5.762 (2.128-15.602), availability of masks (P-value = 0.024) with POR 3.185 (1,259-8.054) and media information (P-value = 0.016) with a POR of 3.578 (1.362-9.393).